Bacterial Vaccinations in Patients with Chronic Obstructive Pulmonary Disease - Dóra Paróczai; Katalin Burian; Andras Bikov (Vaccines, 2024)
Chronic obstructive pulmonary disease (COPD) is a frequent, often progressive, chronic disease of the lungs. Patients with COPD often have impaired immunity; therefore, they are prone to chest infections, such as pneumonia or bronchitis. Acute exacerbations of COPD are major events that accelerate disease progression, contributing to its symptoms’ burden, morbidity, and mortality. Both pneumonia and acute exacerbations in COPD are caused by bacteria against which there are effective vaccinations. Although the number of randomised controlled studies on bacterial vaccinations in COPD is limited, national and international guidelines endorse specific vaccinations in patients with COPD. This review will summarise the different types of vaccinations that prevent pneumonia and COPD exacerbations. We also discuss the results of early phase studies. We will mainly focus on Streptococcus pneumoniae, as this bacterium was predominantly investigated in COPD. However, we also review studies investigating vaccinations against Haemophilus influenzae, Moraxella catarrhalis, and Bordetella pertussis.